A case-control, mono-center, open-label, pilot study to evaluate the feasibility of therapeutic touch in preventing radiation dermatitis in women with breast cancer receiving adjuvant radiation therapy. Issue 4 (August 2015) - Younus, Jawaid; Lock, Michael; Vujovic, Olga; Yu, Edward; Malec, Jitka; D'Souza, David; Stitt, Larry
Highlights We examined the effect of therapeutic touch in prevention of radiation dermatitis. Every patient offered the study accepted it. Radiation dermatitis worst grade and time to develop it remained unchanged. Quality of life, fatigue and mood measurement were largely unaffected.